Analysis of risk factors for massive intraoperative bleeding in patients with placenta accreta spectrum - Wang, Yuanyuan; Zhou, Yadan; Zeng, Lin; Chen, Lian; Zhao, Yangyu (BMC pregnancy and childbirth, 2022)
To analyze relevant factors for massive postpartum hemorrhage in women with placenta accreta spectrum in order to improve the ability to identify those at risk for intraoperative bleeding and improve outcome. This study is a retrospective study and based on data from Hospital electronic medical record. Placenta accreta patients who delivered by cesarean section at Peking University Third Hospital from September 2017 to December 2019 were selected and included. According to the amount of intraoperative bleeding, they were categoried into the massive bleeding group (bleeding volume ≥ 2000 mL, 68 cases) and non-massive bleeding group (bleeding volume < 2000 mL, 99 cases). Univariate analysis and multivariate logistic regression were used to analyze the correlations between related risk factors or ultrasound imaging characteristics and the severity of bleeding during operation. (1) There were statistically significant differences in gravidity, parity, number of prior cesarean deliveries and placenta accreta ultrasound scores (P < 0.05) between the two groups of patients. (2) Among the ultrasonographic indicators, the disappearance of the post-placental clear space, the emergence of cross-border blood vessels in the region of subplacental vascularity, interruption or disappearance of the bladder line, and the presence of the cervical blood sinus had the most significant correlation with hemorrhage during PAS (P < 0.05). The presence of cervical blood sinus, interruption or disappearance of bladder line, the disappearance of the post-placental clear space and abnormal subplacental vascularity are independent risk factors for massive hemorrhage during PAS. We should pay more attention to these indicators in prenatal ultrasound examination in order to reduce the intraoperative bleeding and improve maternal outcomes.